The Strategy of Enhancing Employee Reward Using TOPSIS Method as a Decision Support System - Untung Rahardja; Ninda Lutfiani; Sudaryono Sudaryono; Rochmawati Rochmawati (IJCCS (Indonesian Journal of Computing and Cybernetics Systems), 2020)
Giving rewards for good performance and achievement of tasks needs to be done as a form of recognition and appreciation by the organization/institution to employees, as well as being part of the process of achieving organizational goals. This study aims to develop a Decision Support System that uses the Technique for Order of Preference by Similarity (TOPSIS) method with the PHP programming language to select reward recipients at University. The data used came from 2 groups, namely educational staff (lecturers) and non-educative staff (employees). Determination criteria applied to the educative group are 10 things, namely: tenure, DP3 value, the value on the percentage of work attendance, value on the percentage of teaching attendance, value on lecturer functional position, value on research implementation, the value on implementation of community service, value on the results of the questionnaire by students, the value of employment status, and the value of sanctions. There are 5 determinant criteria used in the non-educative group, namely: tenure, DP3 value, percentage of work attendance, the value of employment status, and value of sanctions. The results of this study are in the form of an information system program as a decision-making tool for the process of selecting reward recipient employees.